DIAGNOSIS AND PREVENTION OF ZOOANTHROPONOSIS (COENUROSIS, ECHINACOCCOSIS, CYSTICERCOSIS) - Tojimurat Gaznakulov; Sherzod Aminjonov; Tursunmurod Achilov; Zohid Alikulov; Alisher Khushnazarov; Madina Klichova (Bright Mind Publishing, 2025)
In the article, Hall (1910) wrote about the development of Multiceps multiceps in the organism of dogs, which are the main spreaders of the disease of cenurosis, and the fact that dogs are the main cause of the spread of this disease, 100 years ago. According to him, multiceps develops only in the dog's intestine. That's why it was noted that dogs play an important role in the origin and development of cenurosis. Among the regions, the multiceps infection of dogs was more common in the mountain-foreland region, and in the desert region, the results of the infection of herd dogs, the infection of village dogs, and the results of the infection depending on the seasons were highlighted. The work of the authors clearly shows that the animals belonging to the dog family, that is, wolves, foxes, jackals and cats, play a secondary role in the spread of the disease, and that they do not have an important role in the spread of cenurosis in nature.